2020
DOI: 10.1371/journal.pone.0236565
|View full text |Cite
|
Sign up to set email alerts
|

Two responses to MeJA induction of R2R3-MYB transcription factors regulate flavonoid accumulation in Glycyrrhiza uralensis Fisch

Abstract: Flavonoids are key components of licorice plant that directly affect its medicinal quality. Importantly, the MYB family of transcription factors serves to regulate the synthesis of flavonoids in plants. The MYB transcription factors represent one of the largest families of transcription factors in plants and play important roles in the process of plant growth and development. MYB gene expression is induced by a number of plant hormones, including the lipid-based hormone jasmonate (JA). Methyl jasmonate (MeJA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 61 publications
(74 reference statements)
0
18
0
Order By: Relevance
“…Jasmonic acid (JA) is a phytohormone ubiquitous in the plant kingdom [ 43 ] that regulates biological processes and secondary metabolite pathways in plants, including flavonoid biosynthesis [ 43 , 44 ]. Active jasmonate (JA-Ile) can induce the degradation of transcriptional repressors called the jasmonate ZIM-domain (JAZ) mediated by the SCF-COI1 complex, thus releasing the transcription factor MYC2 to play a regulatory role in gene expression [ 45 ].…”
Section: Hormones and The Gravitropic Response In Gymnospermsmentioning
confidence: 99%
“…Jasmonic acid (JA) is a phytohormone ubiquitous in the plant kingdom [ 43 ] that regulates biological processes and secondary metabolite pathways in plants, including flavonoid biosynthesis [ 43 , 44 ]. Active jasmonate (JA-Ile) can induce the degradation of transcriptional repressors called the jasmonate ZIM-domain (JAZ) mediated by the SCF-COI1 complex, thus releasing the transcription factor MYC2 to play a regulatory role in gene expression [ 45 ].…”
Section: Hormones and The Gravitropic Response In Gymnospermsmentioning
confidence: 99%
“…In Salvia miltiorrhiza , SmMYB1 enhances the biosynthesis of phenolic acid by increasing the expression of CYP98A14 , CHI , and ANS genes [ 38 ]. In Glycyrrhiza uralensis Fisch., two R2R3-MYB TFs, GlMYB4 and GlMYB88, positively regulate the biosynthesis of flavonoids in licorice cells [ 39 ]. Our previous study has identified an R2R3-type TmMYB3 that is involved in the phloem-specific accumulation of taxol by regulating the expression of the TBT and TS genes [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids are a large category of secondary metabolites ubiquitous in medicinal plants. Flavonoids biosynthesize through the phenylpropanoid pathway from substrate phenylalanine initially which is then converted to cinnamic acid through PAL catalysis ( Ferrer et al, 2008 ; Li et al, 2020 ). We found that the expression of PAL genes was higher in ACS vs. AC.…”
Section: Discussionmentioning
confidence: 99%